Integrating halal tourism with sustainable development goals through Islamic values environmental responsibility and technological innovation - Nohman Khan; Mohammad Falahat; Ihtisham Ullah; Huma Sikandar; Nguyen Thuy Van (Discover Sustainability)
Abstract This study examines the integration of halal tourism with global sustainability frameworks, particularly the United Nations Sustainable Development Goals (SDGs). Using PRISMA methodology, we analyzed 62 peer-reviewed publications from 2019 to 2025, employing bibliometric analysis and structural topic modeling to map research trends in this rapidly expanding field. Three distinct research domains emerged: halal tourism and sustainability integration, SDG alignment, and technology systems. However, analysis revealed field fragmentation, with researchers specializing in individual domains rather than developing comprehensive approaches that bridge religious compliance, environmental responsibility, and technological innovation. This specialization—where scholars focus exclusively on either religious, sustainability, or technological dimensions—creates missed opportunities for integrated sustainable halal tourism implementation. The study’s theoretical contribution lies in developing an integrated conceptual framework connecting previously fragmented research areas, demonstrating how Islamic environmental stewardship principles can enhance rather than constrain sustainability initiatives. This framework transcends the conventional dichotomy between religious requirements and environmental goals. Practically, findings provide actionable guidance: policymakers should develop coordinated frameworks addressing infrastructure challenges; tourism operators can implement certification systems signaling both halal compliance and sustainability commitments; financial institutions can leverage Sharia-compliant instruments supporting sustainable tourism development. The research highlights halal tourism’s significant potential to contribute meaningfully to global sustainability objectives while preserving religious authenticity. Future research should prioritize interdisciplinary studies integrating technological innovations with religious compliance and expand geographical coverage beyond Southeast Asia.